Long working hours among hospital-employed obstetricians and gynecologists and associated factors: a comparative study based on a nationwide survey - Masatoshi Ishikawa; Ryoma Seto; Michiko Oguro; Yoshino Sato (Environmental and Occupational Health Practice)
Objectives: To elucidate the status of reduction in working hours following physician work-style reforms and factors associated with long working hours. Methods: A nationwide questionnaire survey was conducted among obstetricians and gynecologists (OB/GYNs) working in hospitals. The survey elucidated actual working conditions, including working hours and number of out-of-hour (OOH) shifts. To identify factors associated with long working hours, a multivariate logistic regression analysis was performed, with ≥60 or ≥80 working hours per week as dependent variables and OB/GYNs attributes (sex, age, job position, hospital type by ownership, total number of hospital beds, and regional characteristics) as independent variables. Results: Questionnaires were sent to 1,170 hospitals. Valid responses were obtained from 1164 OB/GYNs at 423 hospitals (response rate: 36%): 26.0% worked ≥60 hours per week, a reduction from 58.1% in 2019 (equivalent to over 960 hours of overtime annually), 5.4% worked ≥80 hours per week, a reduction from 41.2% in 2019 (equivalent to over 1,920 hours of overtime annually); and 46.9% worked OOH shifts ≥5 times per month. Factors significantly associated with long working hours per week included male sex, resident position, teaching duty, and number of OOH shifts. Conclusions: Although the working hours of OB/GYNs have decreased because of physician work-style reforms initiated in 2019, long working hours persist. To ensure health of OB/GYNs and patient safety, it is necessary to actively promote physician work-style reforms and advance measures aimed at the centralization of medical resources and addressing their maldistribution.